Age, growth and mortality of common carp (Cyprinnus carpio linneaus, 1758) population in almus dam lake (Tokat-Turkey) - Karataş, Mehmet; Cıcek, Erdogan; Basusta, Asıye; Başusta, Nuri (My University, 2007)
This study was carried out between October 2002 to September 2003 in Almus Dam Lake. A total of 308 Common Carp were fished by monthly sampling and examined. Age composition varied from I to V, and they were composed of 48.3% females, 50.7% males. Mean total length and weight values for females, males and their pooled data were calculated as follows 22.45±2.57cm-150.12±56.05 g, 24.33±3.27cm-213.67±107.82 g and 23.55±3.14 cm-187.38±95.27 g respectively. In addition to this, the calculated length-weight relationships were estimated as W=0.0070L3.2136 for females, W=0.0053*L3.2771 for males and W=0.0049*L3.3191 for their pooled data. Growth parameters of the population: L∞=46.39 cm, K=0.153 year-1 and to=-1,922. The relationship between fork length and total length were calculated as TL=1.0439*FL+0.1626 for females, TL=1.0256*FL+0.6261 for males and TL=1.035*FL+0.3917 for pooled data. Fulton’s Condition Factor and Phiprime values were estimated as K=1.338 and Ф′=5.80 respectively. Total mortality (Z) and natural mortality (M) rates were estimated as 0.64 year and 0.32 year respectively. Exploitation rate (E) was calculated as 0.50.
Keywords: Tokat; Turkey; Cyprinus carpio; mortality; growth; age; carp; dams; freshwater fishes; Almus Dam Lake